Electrophysiological deficits in the retina of the DBA/2J mouse - Scholz, Michael; Kremers, Jan; et al. (Documenta Ophthalmologica, 2009)
The DBA/2J (D2J) is a genetic mouse model for glaucomatous neurodegeneration because the animals develop anatomical and functional retinal deficits that partially can be correlated with elevated intraocular pressure (IOP). The IOP starts to increase at an age of about 6 months as a result of morphological changes within the anterior eye segment, e.g., pigment dispersion and iris synechiae. The purpose of the present study was to investigate how ERG responses change in individuals at different ages in D2J mice and to compare these changes with normal aging effects in pigmented C57/B6 (B6) mice. IOP was measured in awake, non-sedated D2J and B6 mice with a rebound tonometer. At ages between 2-3 and 10 months, scotopic flash ERGs were measured five times with about 2 months' intervals. In addition, light adapted flicker ERGs were recorded. Our data show that the D2J shows lower flicker ERG responses than the B6 mice already at an age of 2-3 months. Dark adapted flash ERG responses are not decreased at this age. In both mouse strains the ERG responses decrease as a function of age, but there is a stronger decrease in the D2J mice. The data of flicker ERGs suggest the presence of early functional deficits in the D2J retina that possibly have a post-receptoral origin. The scotopic flash ERG reveals a functional deficit that occurs at a later stage and that possibly is IOP dependent. But, the deficits appear at an age at which the IOP is still lower than in the B6 mouse, indicating that other factors play an additional role. © 2009 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2009.med.AI.LAIPDL.electr
Keywords: DBA/2J mouse; Electroretinography; Flash ERG; Flicker ERG; Glaucoma; Intraocular pressure